(untitled) (Research, Society and Development, 2024)
Introduction: Among the active learning methods, TBL (Team-based Learning) is an educational strategy consisting of a set of sequenced teaching and learning practices that aims to promote the development of high-performance learning teams and the involvement in meaningful learning tasks. Objective: To analyze issues related to the use of TBL in medical education. Methodology: This is an integrative review, carried out in indexed databases, searching for articles using descriptors. Studies with publications at national and international level were used as inclusion criteria, mainly those that addressed the theme and answered the guiding question, aiming for research focusing on the period from 2012 to 2022. After analysis, 34 articles were selected, these were filtered and analyzed according to authorship, title, year of publication and content, with 29 chosen for final analysis, construction of the theoretical framework and conclusion of the study. Results: The articles generally explain how the method works, as well as the experience reports bring numerous positive points. There is unanimity regarding the effectiveness of the method from different perspectives and situations, some authors reinforce the importance of using mixed methodologies, which combine TBL with several other teaching methodologies and several studies report satisfaction in the teaching-learning process, especially when compared to traditional teaching methods. Conclusion: It is concluded that the challenges to be faced in the transformation of medical education can be facilitated by in-depth studies on the application of the TBL method, including digital tools as process facilitators.